Chemometric study of biological activities of 10 aromatic Lamiaceae species' essential oils. (22nd February 2016) - Djaković Sekulić, Tatjana; Božin, Biljana; Smoliński, Adam
Abstract : The application of chemometric approaches in the comparison of the activity and the chemical composition of essential oils of 10 aromatic Lamiaceae species ( Melissa officinalis, Mentha piperita, Mentha aquatica, Mentha longifolia, Ocimum basilicum, Origanum vulgare, Rosmarinus officinalis, Salvia officinalis, Salvia nemorosa, and Thymus vulgaris ) is reported in this paper. The standard methodology of principal component analysis needs too many principal components (PCs) to effectively describe the relationships between studied samples. PC1 explains only 47.58% of the total variance reflecting the most significant differences between essential oils of S .  nemorosa and Or .  vulgare . PC2 explains 19.77% of the total variance and shows the most significant differences between the essential oils of M .  aquatica compared with those of S .  nemorosa, S .  officinalis and Or .  vulgare . Efficient compression of the data was possible by hierarchical clustering analysis (HCA) complemented with a color map. HCA shows that essential oils of both investigated representatives of genus Salvia are characterized by a high content of oxygenated sesquiterpenes and remarkable antifungal activities, but low antibacterial and antioxidant activity, particularly for the S .  officinalis . Unlike sage, the essential oils of oregano and thyme have high content of aromatic oxygenated monoterpenes and low antifungal but pronounced antibacterial activity. Peppermint, basil, rosemary, and lemon balm are characterized by high content of oxygenated monoterpenes and aliphatic components as well as by high antioxidant 2, 2‐diphenyl‐1‐picrylhydrazil activity of essential oils. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A chemometric approach is described for the comparison of the activity and the chemical composition of the essential oils of 10 aromatic Lamiaceae species. Three clusters were obtained; the first with representatives of genus Salvia (with high content of oxygenated sesquiterpenes and remarkable antifungal but low antibacterial and antioxidant activity); the second (oregano and thyme) with high content of aromatic oxygenated monoterpenes and low antifungal but pronounced antibacterial activity; and the third (peppermint, basil, rosemary, and lemon balm) with high content of oxygenated monoterpenes, aliphatic components, and high antioxidant activity.